PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL ADAPTIF PADA TEMA GERAK DALAM KEHIDUPAN TERHADAP KOMPETENSI IPA SISWA KELAS VIII SMPN 13 PADANG - Rahmi Agustia Widestra; Djusmaini Djamas; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2018)
In 2st century education teaching shouls be four main principles. The main principles are teaching should be student-centered, collaborative, have context and integrated with society. The real condition in the school teaching has not done according to the demands of 21st century education, it needs an appropriate and effective model to solve the problem. A solution of this problem is to investigate the effect of adaptive contextual teaching model of motion in life  theme to improve competence of grade VIII students in science subject. This research used quasi experiment method with randomized control-group only design. The population of this research was students of grade VIII SMPN 13 Padang registered in the academic year 2017/2018. Sampling technique which used in this research was purposive sampling. The research instruments   which used were observation sheet for attitude competence, written test for knowledge competence, and performance assesment skill competence. Hypothesis test used comparison test. The results of this research is the implementation of adaptive contextual teaching model gives a significant effect on the science achievement of students science competence in attitude, knowledge and skill aspect.